A firm-side perspective on parental leave - Huebener, Mathias,Jessen, Jonas,Kühnle, Daniel,Oberfichtner, Michael (IZA - Institute of Labor Economics, 2021)
Motherhood and parental leave interrupt employment relationships, likely imposing costs on firms. We document that mothers who are difficult to replace internally take shorter leave and that their firms hire replacements more often. Introducing more generous parental leave benefits erases the link between mothers' internal replaceability and their leave duration. In firms with few internal substitutes this reduces employment in the short-, but not longer-term. Firms respond by hiring fewer women of childbearing age into occupations where they are difficult to replace internally. Taken together, motherhood and generous parental leave policies burden firms that have few internal substitutes available.
10419/236509
Keywords: Graue Literatur; parental leave; worker absences; firm-specific human capital; substitution; statistical discrimination